Description of two new cryptic species related to Halpe gamma Evans, 1937 from China (Hesperiidae, Hesperiinae) - Xue, Guo-Xi; Li, Meng; Liu, Zhi-Fa; Li, Jia-Ling; Wang, Hong-Min (Zootaxa, 2025)
Two new species, namely Halpe inayoshii sp. nov. from Hainan and H. hsuyufengi sp. nov. from Guangdong and Guangxi of China, are described based on diagnostic differences in the 658 bp COI gene sequence and adult morphology, as compared to H. gamma Evans, 1937. Differences in the wing patterns and genitalia of the three species are explained and illustrated.